Using a new synthetic analogue of prostaglandin E2 "The sulprostone" frustrated in inducing abortion. - Redhead Zapata, Roberto (2015)
Prostaglandins were first recognized for its effects on contractility of uterine muscle fiber and other smooth muscles. But they were isolated in pure form, despite great efforts, until the late 50's and early 60's it is known now that comprise a group of hydroxylated fatty acids chemically connected in a long chain. Each is derived from prostanoic acid, consisting of a 5- coals (cyclopentane) with 2 hydrocarbon chains attached to neighboring carbon.